ATTENTION DEFICIT SYNDROME IN CHILDREN AND WAYS TO PSYCHOLOGICALLY CORRECT IT. - Ibragimova Aziza (Scholar Express Journal, 2023)
Attention Deficit Syndrome (ADS) is a common neurodevelopmental disorder that affects children's ability to focus, control impulses, and maintain attention. This article explores the concept of ADS in children and provides insights into various psychological correction strategies that can help children manage their symptoms and lead more fulfilling lives.
Keywords: Attention deficit syndrome; children; ADHD; behavioral therapy